ナンキョク ロケット ニヨル デンリソウ ジバ ノ カンソク b. デンバ ト デンリュウ ケイ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 遠山, 文雄; トオヤマ, フミオ; 青山, 巌; アオヤマ, イワオ; 小松, 誠一; コマツ, セイイチ; TOHYAMA, Fumio; AOYAMA, Iwao; KOMATSU, Seiichi (1980)
P(論文) 1976年8月17日および9月1日に南極昭和基地から打ち上げられた観測ロケット,S-210JA-24および25号機に3成分フラックスケート型磁力計が搭載され,電離層磁場観測が行われた.その結果,オーロラ出現中の電離層には,いくつかの電流層が存在し,電流の大きさは強くしかも局所的に存在している.24号機においては,上昇時92-100kmに大規模な水平電流層と113km付近の局所的な層が観測され,電流方向は西向きであった.25号機においては,いずれも小規模な層が,上昇時約123km,下降特約117kmに存在しており,さらに88-108kmにかけて大きな磁場変動が観測された. Geomagnetic field variations in the ionosphere were measured by the three axial fluxgate magnetometers on board the two sounding rockets, S-210JA-24 and 25,which were launched on August 17 and September 1, 1976 at Syowa Station, Antarctica, respectively. From the measured magnetic field data, It is found that there are a large-scale horizontal current layer at 92-100 km and a local current layer at 113 km during the ascent of the S-210JA-24 rocket. Two small-scale current layers were measured at the height of 123 km during the descent of the S-210JA-25 rocket. And a large field variation was obtained at the heights between 88 and 108 km during the descent of the S-210JA-25 rocket departmental bulletin paper